The Evolving Role of TRAFs in Mediating Inflammatory Responses - Dhillon, Bipandeep; Aleithan, Fatemah; Abdul-Sater, Zahi; Abdul-Sater, Ali A. (Frontiers in Immunology, 2019)
TRAFs (tumor necrosis factor (TNF) receptor associated factors) are a family of signaling molecules that function downstream of multiple receptor signaling pathways and play a pivotal role in the biology of innate and adaptive immune cells. Following receptor ligation, TRAFs generally function as adapter proteins to mediate the activation of intracellular signaling cascades. With the exception of TRAF1 that lacks a Ring domain, TRAFs have an E3 ubiquitin ligase activity which also contributes to their ability to activate downstream signaling pathways. TRAF-mediated signaling pathways culminate in the activation of several transcription factors, including nuclear factor-B (NF-B), mitogen-activated protein kinases (MAPKs; e.g. ERK-1 and ERK-2, JNK and p38), and interferon-regulatory factors (IRF; e.g. IRF3 and IRF7). The biological role of TRAFs is largely due to their ability to positively or negatively regulate canonical and noncanonical NF-B signaling. While TRAF-mediated signaling regulates various immune cell functions, this review is focused on the recent advances in our knowledge regarding the molecular mechanisms through which TRAF proteins regulate, positively and negatively, inflammatory signaling pathways, including Toll–IL-1 receptors, RIG-I like receptors and Nod-like receptors. The review also offers a perspective on the unanswered questions that need to be addressed to fully understand how TRAFs regulate inflammation.